Strategi Tuan Guru Masnun Tahir Dalam Mencegah Berkembangnya Radikalisme di Indonesia - Arif Sugitanata, Siti Aminah, Suud Sarim Karimullah (Sekolah Tinggi Ilmu Kepolisian, 2023)
This article discusses Mitigating Radicalism in Religion: Tuan Guru Masnun Tahir's Strategy in Preventing the Development of Radicalism in Indonesia. The purpose of this research is to analyze the efforts of Tuan Guru Masnun Tahir in preventing the development of radicalism in Indonesia. In this study, researchers made use of literature studies with data derived from books and scientific journals. According to Tuan Guru Masnun Tahir, there are five preventive steps to prevent the development of radicalism, namely deepening religious understanding, increasing morality or morals, inculcating peace-based education, reorienting patterns of diversity in the people, efficiency of the role of public figures.